2002
DOI: 10.1177/03635465020300012401
|View full text |Cite
|
Sign up to set email alerts
|

Knee Arthroscopy with the Use of Local Anesthesia—An Increased Risk for Repeat Arthroscopy?

Abstract: Although there have been many reports of good results when local anesthesia is used with knee arthroscopy, it is not used as a standard anesthetic. Concerns about local anesthesia include the fear of prolonged surgery, which could result in inadequate anesthesia, thus causing the patient unnecessary discomfort. The purpose of this study was to evaluate the risk of repeat arthroscopy and the patient satisfaction rate up to 6 months after knee arthroscopy under local anesthesia. In this prospective, randomized s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 7 publications
2
8
0
1
Order By: Relevance
“…Nevertheless, we find it important to study health care from an economic point of view, and to share experiences in order to produce as cost-effective health care as possible. In an earlier publication we showed that arthroscopy in LA is a safe procedure, with a similar clinical outcome to that achieved with arthroscopies in GA/SA [5,8,9]. Results of the present study show that arthroscopy in LA was both more cost-and time-effective than arthroscopy in SA/GA in our setup.…”
Section: Discussionsupporting
confidence: 80%
“…Nevertheless, we find it important to study health care from an economic point of view, and to share experiences in order to produce as cost-effective health care as possible. In an earlier publication we showed that arthroscopy in LA is a safe procedure, with a similar clinical outcome to that achieved with arthroscopies in GA/SA [5,8,9]. Results of the present study show that arthroscopy in LA was both more cost-and time-effective than arthroscopy in SA/GA in our setup.…”
Section: Discussionsupporting
confidence: 80%
“…Knee arthroscopy has been widely accepted as the most important method to diagnose and treat knee diseases, and is characterized by sound diagnosis and minimal invasion during the surgery. Arthroscopic surgery of the knee is preferred by the majority of properly selected and well‐informed patients. Postoperative stay after the surgery is significantly shorter in patients receiving local anesthesia than general anesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…However there is concern that local anesthesia may not provide adequate pain control and may lead to increase in operative difficulties and reoperation rate and patient dissatisfaction [1,17].…”
Section: Introductionmentioning
confidence: 99%